2019
DOI: 10.1039/c9ra02881a
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-assisted sorption of Pb(ii) on multi-walled carbon nanotube in presence of natural organic matter: an insight into main and interaction effects using modelling approaches of RSM and BRT

Abstract: The proposed mechanism for effect of HA on Pb(ii) removal using MWCNTs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…Subsequently, to further explore the interaction of important biochemical indicators, the interaction was studied more simply and maturely according to the BRT and GAM models [17,18]. It has been shown that a decrease in iron stores is associated with an increase in glycated hemoglobin A1c (HbA1c) [19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, to further explore the interaction of important biochemical indicators, the interaction was studied more simply and maturely according to the BRT and GAM models [17,18]. It has been shown that a decrease in iron stores is associated with an increase in glycated hemoglobin A1c (HbA1c) [19][20][21].…”
Section: Discussionmentioning
confidence: 99%